Physically based model for assessing rainfall-induced deep-seated landslides using a hydrological-geotechnical model - Sartsin Phakdimek; Daisuke Komori; Thapthai Chaithong; Yuta Abe (Annals of GIS)
In mountainous areas, understanding the sizes and types of rainfall-induced landslides, and identifying areas at high risk, are critical challenges for disaster management. Shallow and deep-seated landslides are the two major types in mountainous regions, distinguished by their failure mechanisms, geomaterials, depths and sizes. Shallow landslides typically involve planar failures at depths less than 3 m. In contrast, deep-seated landslides exhibit ellipsoidal or hemispherical geometries, with rotational failure planes exceeding 3 m in depth. The infinite slope stability model is commonly used to analyse shallow landslides, but it tends to overestimate the occurrence of deep-seated landslides due to its unsuitability for ellipsoidal or hemispherical failure surface geometries. To address this issue, this study proposes modifying the slope stability model by incorporating a hemispherical shape aligned with the failure characteristics of deep-seated landslides as hemispherical slope stability. This is coupled with infiltration and groundwater recharge analysis, and is used to simulate rainfall-induced deep-seated landslides induced within GIS environment. Model validation was conducted by comparing the predictions of the hemispherical slope stability model with historical landslide data and the traditional Scoops3D model, using ROC-AUC values. The hemispherical slope stability model demonstrated good agreement with historical data, achieving AUC values of 81.08% to 83.85%, and showed consistent results with the Scoops3D model in predicting stable and unstable zone. Therefore, these advancements are particularly valuable for real-time application as they enable the precise delineation of landslide susceptibility area.